2023
DOI: 10.3390/ani13203266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Types of Dietary Fibers on Lipid Metabolism and Bile Acids in Weaned Piglets

Yaolian Hu,
Dongting He,
Bing Yu
et al.

Abstract: The aim of this study was to investigate the effects of dietary fiber on the serum biochemistry, bile acid profile, and gut microbiota in piglets. Twenty-four pigs (initial body weight: 10.53 ± 1.23 kg) were randomly divided into three treatments with eight replicate pens of one pig per pen for 21 d. The dietary treatments consisted of the following: (1) a fiber-free diet (NS); (2) a fiber-free diet + 3% fructooligosaccharides (SI); (3) a fiber-free diet + 3% dietary fiber mixture (fructooligosaccharides, long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…65 High dietary fiber intake has been reported to decrease the levels of secondary bile acids, for instance, a previous study found that the use of 3% dietary fiber decreased the GDCA level in the bile of piglets and was associated with the serum TC concentrations. 66 Similar to our findings, studies have shown that high-fiber diets or resistant-starch diets resulted in lower levels of DCA or LCA in the large intestine, and could be explained by the changed colonic bacterial species. 17 Therefore, the changed colonic bile acid profile upon supplementation with high konjac glucomannan amounts was responsible for the improvement of hepatic lipid and glucose homeostasis as well as the intestinal microbiota profile of mice.…”
Section: Discussionsupporting
confidence: 91%
“…65 High dietary fiber intake has been reported to decrease the levels of secondary bile acids, for instance, a previous study found that the use of 3% dietary fiber decreased the GDCA level in the bile of piglets and was associated with the serum TC concentrations. 66 Similar to our findings, studies have shown that high-fiber diets or resistant-starch diets resulted in lower levels of DCA or LCA in the large intestine, and could be explained by the changed colonic bacterial species. 17 Therefore, the changed colonic bile acid profile upon supplementation with high konjac glucomannan amounts was responsible for the improvement of hepatic lipid and glucose homeostasis as well as the intestinal microbiota profile of mice.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the expression of L-tyrosine in the serum of sows fed with different CSSF was increased, and the thickness of backfat was decreased, indicating that CSSF could regulate body health by promoting fat degradation. Moreover, a fiber-rich diet could enhance lipid metabolism ( 56 ), amino acid metabolism ( 57 ), and cofactor and vitamin metabolism ( 58 ). The KEGG enrichment analysis performed in this study emphasized these metabolic pathways, suggesting that CSSF could maintain body homeostasis by regulating lipid metabolism, amino acid metabolism, cofactor and vitamin metabolism.…”
Section: Discussionmentioning
confidence: 99%